THE INFLUENCE OF WORK COMPETENCE AND INFRASTRUCTURE ON CUSTOMER SATISFACTION THROUGH SERVICE QUALITY AT THE SRI BINTAN PURA TANJUNGPINANG PORT PASSENGER TERMINAL - Fajar Ardhi Gibran; Lira Agusinta; HM. Thamrin; Endang Sugiharti; Prasada Ricardianto (Bajang Institute, 2024)
This research aims to analyze the influence of variables, namely work competency, facilities and infrastructure on customer satisfaction through service quality at Sri Bintan Pura Tanjungpinang Port. The sample in this research was 500 passengers at the Sri Bintan Pura Port passanger Terminal Tanjungpinang. The data analysis method used in this research is Structural Equal Model Partial least Square. These technique will be used in data analysisand become an integral part of the overall data analysis in this research. Data analysis was carried out in three stages, namely the description stage, the analysis requirements testing stage, and the hypothesis testing stage. It can be concluded that Work Competence and Infrastructure have a positive and significant influence on Customer Satisfaction at Sri Bintan Pura Tanjungpinang Port, both directly and through the mediation of Service Quality. Work Competencies have a greater influence than Infrastructure on Customer Satisfaction. Service Quality plays an important role as a mediator, strengthening the influence of Work Competency and Infrastructure on Customer Satisfaction